Energy enhancement of aged photovoltaic array under hotspot conditions : A comparison of different interconnection topologies - Al Mansur, Ahmed; Alam, Md Sabbir; Leyon, Shaquar Islam; Sultana, Zinat; Islam, Md Imamul; Haider, Chowdhury Shajjad; Tohid, Sabbir Hasan; Rahman, Md. Mostafizur; Alom, Md Shahin; Sultana, Shafia; Ustun, Taha Selim (Institute of Electrical and Electronics Engineers Inc., 2023)
Aged photovoltaic panels commonly have hotspots, which can result in large power losses. In this study, hotspot creation in solar panels is investigated and the reasons for it are identified and outlines many methods for preventing the establishment of pre-hotspots and investigates the findings of experimental research. The power output, voltage, current, irradiance, and loss percentage for five configurations of solar array designs have been investigated in this work using a 4×4 array consisting of 16 PV modules that are 4 years old. Experimentally it can be possible to recover the output power by changing interconnections such as SP, TCT, LD, BL, and HC. The output demonstrates that the loss of SP, TCT, LD, BL, and HC was 8.81 %, 4.06%, 0.06%, 5.37%, and 3.13% respectively. 4.286% is the average loss percentage for all five configurations. The recoverable power of the TCT, LD, BL, and HC concerning SP was 5.21 %, 9.73%, 3.77%, and 6.24% respectively. The findings demonstrate the LD configuration has the lowest percentage of power loss, and the maximum loss has been obtained by the SP configuration.